Plasmablastic lymphoma exclusively involving bones mimicking osteosarcoma in an immunocompetent patient: A case report. Issue 28 (July 2016) - Sarker, Azmal Kabir; Im, Hyung-Jun; Paeng, Jin Chul; Cheon, Gi Jeong; Kang, Keon Wook; Chung, June-Key; Lee, Dong Soo
Abstract: Background: It has been known that plasmablastic lymphoma (PBL) is a neoplasm of immunocompromised patients occurring in soft tissue of oral cavity or in the vicinity whereas bone is an unlikely site to harbor PBL. However, its occurrence is increasingly being reported in immunocompetent individuals in either osseous or extra-oral sites. To our best knowledge, F-18 FDG PET/CT findings of PBL involving bones in an immunocompetent patient have not been reported, yet . Case summary: We report a case of PBL involving multiple bones in an immunocompetent patient. Features of different imaging modalities including F-18 Fluoro-deoxy glucose (FDG) positron emission tomography/computed tomography (PET/CT) were correlated well as findings of osteosarcoma in mandible with metastatic lesions. However, the histopathology and immunohistochemistry (IHC) of bone tissues from 2 separate biopsy sites revealed features of PBL. Conclusion: awareness to F-18 FDG PET/CT findings of PBL involving bones in an immunocompetent patient may prevent misdiagnosis.